Predicting intention to invest in Unit Trust among UUM's postgraduate students - Sharif, Zakiyah (Universiti Utara Malaysia, 2008)
Unit trust is one of the investment mechanisms that nowadays have been given much attention by Malaysian government. Principally, investing in unit trust allows every people with or without sound knowledge of investment to invest in any investment vehicle with expectation to generate positive income or return. However, even though many responsible parties including government have done many efforts to encourage Malaysian citizen to invest in unit trust, the result is hampered. In predicting future investment, intention plays important role to predict actual behavior. Therefore, this study is done to examine the intention of the postgraduate students to invest in unit trust.The model of Theory Planned Behavior is used to measure the intention by looking at the three key variables, which are attitudes, subjective norms and perceived behavioral control.212 respondents successfully completed the 19 items questionnaires.Result of the study revealed that only attitudes and subjective norms significantly influence students’ intention to invest in unit trust.However, perceived behavioral control is not significant.The implications to the responsibility parties especially the policy makers are discussed further.